Improving gel properties of egg white protein using coconut endosperm dietary fibers modified by ultrasound and dual enzymolysis combined with carboxymethylation or phosphate crosslinking - Anyu Zhang; Jun Ma; Peiyao Long; Yajun Zheng; Yichan Zhang (Current Research in Food Science)
Coconut endosperm residue is a rich dietary fiber resource; however, its hydration properties are poor. To enhance the functionality and applications of coconut endosperm residue dietary fiber (CERDF) in the food industry, ultrasound, cellulase, and hemicellulase hydrolysis combined with carboxymethylation or phosphate crosslinking have been used. The impact of the modified CERDFs on egg white protein gel (EWPG) was also studied. Compared to unmodified CERDF, CERDF modified by ultrasound and dual enzymatic hydrolysis combined with carboxymethylation (CERDF-UDEC) or phosphate-crosslinking (CERDF-UDEPC) exhibited a larger surface area and improved water retention and expansion abilities (p < 0.05). Addition of CERDF, CERDF-UDEC, and CERDF-UDEPC increased the random coil content of EWPG and rendered its microstructure more granular. CERDF-UDEC and CERDF-UDEPC improved EWPG properties more effectively than unmodified CERDF. These enhancements included increased water retention, pH, hardness (from 109.87 to 222.38 g), chewiness (from 78.07 to 172.13 g), and gumminess (from 85.12 to 181.82), and a reduction in its freeze-thaw dehydration rate (from 33.66% to 16.26%) and transparency (p < 0.05). Adding CERDF and CERDF-UDEC (3–5 g/100 g) enhanced the gastric stability and intestinal digestibility of EWPG. Thus, CERDF modified through ultrasound and dual enzymolysis combined with carboxymethylation or crosslinking improved the gel properties of EWPG. However, further research is needed to clarify the mechanisms behind these modifications and evaluate their economic feasibility.